2012
DOI: 10.5539/ijps.v4n3p62
|View full text |Cite
|
Sign up to set email alerts
|

When Home Isn’t Home – A Study of Homesickness and Coping Strategies among Migrant Workers and Expatriates

Abstract: This paper addresses, homesickness, an important issue in the area of international human resource management. It uses psychological and sociological literature to highlight the negative effects of homesickness on migrant workers and expatriates. These effects range from psychological disruptions to physical manifestations that affect the health and welfare of individuals and impact on work performance. The paper presents a model of coping strategies used by expatriates to deal with homesickness. This model is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 16 publications
2
29
0
5
Order By: Relevance
“…The effect of migration is evident throughout historical and recent literature (Ward 2000, Hack-Polay 2012. Ward (2000) found that migration is related to multiple losses and homesickness, which results in some migrants thinking constantly about their homeland, sleeping badly, refusing to eat food and experiencing physical weakness and anxiety.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The effect of migration is evident throughout historical and recent literature (Ward 2000, Hack-Polay 2012. Ward (2000) found that migration is related to multiple losses and homesickness, which results in some migrants thinking constantly about their homeland, sleeping badly, refusing to eat food and experiencing physical weakness and anxiety.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As demandas percebidas pelos primeiros desbravadores do continente gelado, com relação direta aos impactos psicofisiológicos, foram melancolia e abuso de álcool (Guly, 2012;Paul et al, 2015;Zimmer et al, 2013). Atualmente, os estudos internacionais focam a definição dos tipos de estressores predominantes no contexto ICE (Bishop et al, 2010;Hack-Polay, 2012;Kjaergaard et al, 2013;Palinkas, Keeton, Shea, & Leveton, 2011;Paul et al, 2015;Simpson, 2010;Weiss et al, 2011;Zimmer et al, 2013), ratificados nesta pesquisa.…”
Section: Resultsunclassified
“…A exposição crônica a muitos estressores é comumente observada em missões de longa duração na Antártica, com potenciais impactos negativos na saúde, no desempenho e também em aspectos de segurança do indivíduo e do grupo (Bishop et al, 2010;Hack-Polay, 2012;Kjaergaard, Leon, & Fink, 2013;Simpson, 2010;Zimmer et al, 2013). Entretanto, durante as operações de verão e temporadas de pesquisa, ocorrem eventos estressores reconhecíveis e padrões, conforme estudos observacionais e coleta de relatos de expedicionários (GongGu, Qian, & Che, 2011).…”
unclassified
“…In our study, expatriates reported being frightened by the risk of becoming involved in accidents during their frequent moves from one country to another. In particular, this fear seemed to be greater for traffic accidents ( Wilks et al, 1999 ), but a fear of flying was also described ( Hack-Polay, 2012 ).…”
Section: Discussionmentioning
confidence: 99%